Dlg protein is required for junction structure, cell polarity, and proliferation control in Drosophila epithelia (The Rockefeller University Press, 1996)
The Discs large (Dlg) protein of Drosophila is the prototypic member of a growing family of proteins termed membrane-associated guanylate kinase homologs (MAGUKs). The MAGUKs are composed of a series of peptide domains that include one or three DHR/PDZs, an SH3, and a region homologous to guanylate kinase (GUK). We have previously shown that the product of this gene, the Dlg protein, is localized at the septate junctions between epithelial cells, and that mutations in the gene cause neoplastic overgrowth of the imaginal discs. The dlg locus is therefore defined as a tumor suppressor gene. In this paper, we show that the Dlg protein is localized on the cytoplasmic face of the septate junction and is required for the maintenance of this structure. It is also required for proper organization of the cytoskeleton, for the differential localization of membrane proteins, and for apicobasal polarity of epithelial cells. However, these other functions can be uncoupled from Dlg's role as a tumor suppressor since mutations in two domains of the protein, the SH3 and GUK, cause loss of normal cell proliferation control without affecting the other functions of the protein. These results suggest that, besides regulating cellular proliferation, the Dlg protein is a critical component of the septate junctions and is required for maintaining apicobasal polarity in Drosophila epithelium.